2018
DOI: 10.18632/oncotarget.25524
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic DSF counteracts chemotherapy induced neuropathic pain

Abstract: Problem statement: Chemotherapy-induced peripheral neuropathy (CIPN) is a widespread and potentially disabling side effect of various anticancer drugs. In spite of the intensive research focused on obtaining therapies capable to treat or prevent CIPN, the medical demand remains very high. Microtubule-stabilizing agents, among which taxanes, are effective chemotherapeutic agents for the therapy of several oncologic diseases. The inflammatory process activated by chemotherapeutic agents has been interpreted as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
42
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 49 publications
5
42
0
1
Order By: Relevance
“…Recently, emerging evidence indicated that dietary antioxidants, in particular polyphenols, may exert beneficial effects on the brain, protecting neurons against oxidative stress-induced injury, reducing cardiovascular risk factor, control and suppressing neuroinflammation. 22 The regular inclusion of antioxidants in the diet is really important to maintain the brain health, but it could be difficult especially in elderly. To this purpose, antioxidants dietary supplement may represent an effective strategy to counteract cognitive age-related decline.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, emerging evidence indicated that dietary antioxidants, in particular polyphenols, may exert beneficial effects on the brain, protecting neurons against oxidative stress-induced injury, reducing cardiovascular risk factor, control and suppressing neuroinflammation. 22 The regular inclusion of antioxidants in the diet is really important to maintain the brain health, but it could be difficult especially in elderly. To this purpose, antioxidants dietary supplement may represent an effective strategy to counteract cognitive age-related decline.…”
Section: Discussionmentioning
confidence: 99%
“…The effect could be reversed by gut microbiota restoration and this suggests an influence of the gut microbiota on neuropathic pain (Shen et al, 2017). Another study demonstrated a positive effect of probiotics in vitro on paclitaxel-induced neuropathic pain features (Castelli et al, 2018). However, when probiotics L. reuteri LR06 or Bifidobacterium BL5b were administered to rats with chronic constriction injury-induced neuropathic pain, no effect on pain sensation was observed .…”
Section: Role Of the Gut Microbiota In Disease Symptoms And Pathogenesismentioning
confidence: 99%
“…For example, the De Simone Formulation probiotic (i.e., Bifidobacterium breve, B. longum, B. infantis, Lactobacillus plantarum, L. paracasei, L. delbrueckii subsp. Bulgaricus, L. acidophilus, Streptococcus thermophilus) alleviated chemotherapy-induced neuropathic pain in an in vitro model, but has not been tested yet in vivo [12]. A recent study attempted to use probiotics (i.e., Lactobacillus reuteri lr06 or Bifidobacterium bl5b) to alleviate SNI (spared-nerve injury; a traumatic peripheral nerve injury)-induced neuropathic pain, but failed [42].…”
Section: Introductionmentioning
confidence: 99%